PERUBAHAN SOSIAL PADA KESENIAN TRADISIONAL EBLEG SINGA MATARAM DI KELURAHAN PANJER KECAMATAN KEBUMEN KABUPATEN KEBUMEN - Astriawan, Fikar Idham; Nurcahyono, Okta Hadi; Yuhastina, . (Studi Budaya Nusantara, 2021)
The development of an increasingly modern era has an impact on social changes in all aspects of daily life, one of which is the socio-cultural aspect. The impact of social changes on socio-cultural aspects in modern times can be seen from the number of traditional arts that have decreased in existence, some are even experiencing extinction. This study aims to determine how the social changes that occur in the traditional art of Ebleg Singa Mataram in Panjer Village, Kebumen District, Kebumen Regency, as well as how the community's efforts to maintain this art in modern times. This study uses descriptive qualitative research methods, using purposive sampling technique in determining informants. Data were collected through interviews, observation, and documentation. The theory usedto analyze the research data is Herbert Spencer's theory of social evolution. The results of the data findings show that the changes that occur in the traditional art of Ebleg Singa Mataram are not in terms of the standard of the traditional art ballet. However, the changes that have occurred include the enthusiasm of the audience for thetraditional art of Ebleg Singa Mataram which has increased in size (development) gradually over time. The existence of Ebleg Singa Mataram as the oldest traditional Kuda Lumping art in Kebumen Regency is experiencing complexities, this is due to the adaptation process from several other traditional Kuda Lumping arts communities in Kebumen Regency. In addition, social changes make people differentiate and indirectly the regeneration of the traditional arts community of Ebleg Singa Mataram is hampered.